Enriching Students’ Vocabulary Using Realia of Seventh Grade Students of SMPN 38 Palembang - Alfiah Nur Annisa; Nike Angraini; Badriyah Ulfah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
In English language teaching, vocabulary is included in the four-integrated language skills. One of the media that can be used and is able to increase student interest in learning vocabulary is by using realia. Thus, this study tried to figure out the effectiveness of realia to enrich students’ vocabulary. In conducting this research, the researcher used quantitative methods by using two classes with the name experimental class and control class consisting of 68 students. Pre-test and Post-test were given in both classes, the experimental class was given treatment before the researcher conducted the Post-test, and the control class was not given any treatment. In analyzing the data, the results showed that the experimental class students' vocabulary mastery increased as indicated by the pre-test and post[1]test scores. It means that the t-obtain is bigger than t-table (14,723 > 2,034) and the value of Sig. (2-tailed) was 0.000 < 0.05, then null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It means that there was any significant enrichment of students’ vocabulary being taught by using realia. In addition, the use of realia is suggested for teachers as a media in teaching students’ vocabulary.In English language teaching, vocabulary is included in the four-integrated language skills. One of the media that can be used and is able to increase student interest in learning vocabulary is by using realia. Thus, this study tried to figure out the effectiveness of realia to enrich students’ vocabulary. In conducting this research, the researcher used quantitative methods by using two classes with the name experimental class and control class consisting of 68 students. Pre-test and Post-test were given in both classes, the experimental class was given treatment before the researcher conducted the Post-test, and the control class was not given any treatment. In analyzing the data, the results showed that the experimental class students' vocabulary mastery increased as indicated by the pre-test and post[1]test scores. It means that the t-obtain is bigger than t-table (14,723 > 2,034) and the value of Sig. (2-tailed) was 0.000 < 0.05, then null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It means that there was any significant enrichment of students’ vocabulary being taught by using realia. In addition, the use of realia is suggested for teachers as a media in teaching students’ vocabulary.